The Prevalence and Trends of Hepatitis B, Hepatitis C, and HIV among Voluntary Blood Donors in Kohgiluyeh and Boyer-Ahmad Transfusion Center, Southwestern Iran - Seyed Mehdi SAJJADI; Ali Akbar POURFATHOLLAH; Saeed MOHAMMADI; Bijan NOURI; Rostam HASSANZADEH; Fariba RAD (Tehran University of Medical Sciences, 2018)
Background: Transfusion transmissible infections (TTIs) are a common complication of blood transfusion. Evaluation and monitoring the prevalence rate of TTIs in blood donors is a valuable indicator of donor selection and blood safety. We analyzed the trends of these infections among blood donors at Kohgiluyeh and Boyer-Ahmad transfusion service (KBTC) during 10 years. Methods: Viral screening and confirmatory tests were carried out on 180304 voluntary donations from 2005-2014. The annual prevalence rates of hepatitis B virus (HBV), hepatitis C virus (HCV) and HIV infections per 100000 donations and 95% confidence interval were calculated. Chi-square test was applied to obtain the P-value. Results: The overall prevalence was 0.13% for HBV and 0.06% for HCV while there were only three positive cases for HIV. The annual trend fluctuated during the time period studied. Compared to first-time donors, regular and repeat donors were significantly less likely to be positive for these infections. Outstandingly, this study provides first data in TTIs seropositivity rates among blood donors in our region; surprisingly were lower compared to other reports of Iran. Conclusion: The trends of TTIs prevalence in this study provide additional evidence that safety measures employed by the KBTC have been effective in maintaining a safe blood supply. The lower prevalence of TTIs in our study compared with other Iranian studies and also the general population reflects the efficacy of donor selection and education procedures in KBTC.